Total Product and Total Edge Product Cordial Labelings of Dragonfly Graph Dgn - N. Inayah; A. Erfanian; M. Korivand (Journal of Mathematics)
In this paper, we study the total product and total edge product cordial labeling for dragonfly graph Dgn. We also define generalized dragonfly graph and find product cordial and total product cordial labeling for this family of graphs.